2013
DOI: 10.1007/s00296-013-2835-8
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T cells in Behçet’s disease: Is there a correlation with disease activity? Does regulatory T cell type matter?

Abstract: The aim of this study was to investigate the percentage of regulatory T cells and the correlation with clinical activity in Behçet's disease. Forty Behçet's disease (BD) patients, 18 males and 22 females, were included in the study. The patients were diagnosed according to the published BD criteria. Twenty age- and sex-matched volunteer healthy donors were also included. At the time of sampling, clinical activity was assessed for activity signs and symptoms according to the BD Current Activity Form. We conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…21 Indeed, in the peripheral blood of BD patients, increased concentrations of CD4+CD25+ Treg cells have been detected in subjects with active disease compared with BD patients in remission suggesting a potential attempt of the immune system to counterbalance active inflammation. 22 Despite this finding has not been confirmed by Gündüz et al, 23 who have detected a decreased number of peripheral Tregs in active BD, the involvement of CD4+CD25+ Tregs in uveitis resolution appears compelling both because decreased percentages of Treg cells have been reported to be a predictive marker of ocular attack 24 in BD patients and because this suppressor cell line has been shown to downgrade EAU in the rat. 25 Aside from cellular components, several pro-inflammatory molecules are associated with EAU development: particularly, adhesion molecules are associated with migration of inflammatory cells into the eye.…”
Section: From Experimental Autoimmune Uveitis In the Animal Modelsmentioning
confidence: 95%
“…21 Indeed, in the peripheral blood of BD patients, increased concentrations of CD4+CD25+ Treg cells have been detected in subjects with active disease compared with BD patients in remission suggesting a potential attempt of the immune system to counterbalance active inflammation. 22 Despite this finding has not been confirmed by Gündüz et al, 23 who have detected a decreased number of peripheral Tregs in active BD, the involvement of CD4+CD25+ Tregs in uveitis resolution appears compelling both because decreased percentages of Treg cells have been reported to be a predictive marker of ocular attack 24 in BD patients and because this suppressor cell line has been shown to downgrade EAU in the rat. 25 Aside from cellular components, several pro-inflammatory molecules are associated with EAU development: particularly, adhesion molecules are associated with migration of inflammatory cells into the eye.…”
Section: From Experimental Autoimmune Uveitis In the Animal Modelsmentioning
confidence: 95%
“…The expression of CD4 + CD25 − Foxp3 + T reg cells was observed to be higher in healthy controls compared to clinically active patients but that was not the case when comparing the inactive patients' group to the healthy control group. The percentage of expression of CD4 + CD25 + Foxp3 − T reg cells did not vary when comparing active and inactive patients to healthy controls (Gündüz et al, 2013).…”
Section: Discussionmentioning
confidence: 83%
“…Contrariwise, patients with a decreased percentage of expression of Foxp3 + cells suffered recurrent episodes of acute uveitis (Sugita et al, 2011). Gündüz et al (2013) concluded a similar study by stating that the percentage of expression of CD4 + CD25 + Foxp3 + Treg cells in clinically inactive BD patients or healthy controls was higher compared to active BD patients. The expression of CD4 + CD25 − Foxp3 + T reg cells was observed to be higher in healthy controls compared to clinically active patients but that was not the case when comparing the inactive patients' group to the healthy control group.…”
Section: Discussionmentioning
confidence: 86%
“…Defects in both the relative proportion of Tregs, and individual suppressive function of Tregs to restrain CD4+ and CD8+ T cell-mediated immune responses, have been widely reported to occur in a number of autoimmune diseases, including various types of vasculitis 43,44 . A number of previous reports have sought to address the changes in relative proportion of circulating Tregs in BD patients, generally showing of decreases 45,46,47 in Treg percentages in active BD patients relative to healthy control. Treg percentages in BD patients have also been shown to change substantially in response to treatment 48,49 .…”
Section: Discussionmentioning
confidence: 99%